(untitled) (MAP Kinase, 2015)
JNK is a subfamily of MAP kinases that hat regulates a range of biological processes implicated in response to stress, such as cytokines, ultraviolet irradiation, heat shock, and osmotic shock as well as growth factors like PDGF, EGF, FGF, etc. They were originally identified as kinases that bind and phosphorylate JUN on S63 and Se73 within its transcriptional activation domain. The deregulation of these kinases is shown to be involved in human diseases, such as cancer, immune diseases and neurodegenerative disorders. The realization of the therapeutic potential of the inhibition of JNKs led to a thorough search for small-molecule inhibitors first for research purposes, but later also for therapeutic applications. Here, we discuss some of the most well-known JNK inhibitors and their use in basic research or clinical science.